PENGARUH TUNJANGAN KINERJA DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI NEGERI SIPIL BALAI KARANTINA PERTANIAN KELAS I BANJARMASIN - Liza Hardani; Ahmad Alim Bachri; Dahniar (Universitas Lambung Mangkurat, 2016)
The purpose of this research is: 1. Analyze performance benefits and working discipline simultaneously on the performance of civil servants on Agriculture Quarantine Class I Banjarmasin. 2. Analyze the performance benefits on the performance of civil servants at the Institute for Agriculture Quarantine Class I Banjarmasin. 3. Analyze labor discipline on the performance of civil servants on Agriculture Quarantine Class I Banjarmasin. Explanatory research, the sampling technique using saturated sampling technique with the number of respondents is 66 civil servants. The research instrument used questionnaires and measurement interval scale variable with the characteristics of the respondents were civil servants at the Institute for Agriculture Quarantine Class I Banjarmasin who receive performance benefits since 2012. Allowance performance (X1) and discipline (X2) as independent variables to be tested simultaneously (Simultaneous) influence on the performance of civil servants (Y) as the dependent variable. Examine the effect of direct (partial) performance benefits (X1) on the performance of civil servants (Y) and examine the effect of direct (partial) labor discipline (X2) on the performance of civil servants (Y). The data obtained were analyzed qualitatively and quantitatively by using analytical tools such as validity, reliability, and multiple regression analysis with the classical assumption using multicollinearity test, test heterokedastisitas, test for normality and linearity test, to test the hypothesis by using the F test and t test with IBM SPSS version 19 program. The study states that the benefits of performance (X1) and discipline (X2) positive and significant impact on the performance of civil servants (Y). Performance benefits (X1) significant positive effect on the performance of civil servants (Y) and discipline (X2) significant positive effect on the performance of civil servants (Y).